Praktik Menyusui dan Peran Suplemen serta Makanan Tambahan pada Ibu - Devi Savitri Effendy (Jurnal Kendari Kesehatan Masyarakat, 2024)
Breastfeeding practices are critical for child nutrition, particularly in coastal areas where dietary and socio-economic challenges are common. This study aimed to examine the factors associated with breastfeeding practices among mothers of children aged 6–23 months in Kendari City, Indonesia. A cross-sectional study was conducted from November to December 2024, involving 220 mothers selected through stratified random sampling. Data were collected using a structured questionnaire via Epicollect5. Factors analyzed included maternal, household, and dietary variables. Statistical analyses involved chi-square tests and logistic regression, with a significance level set at p-value <0.05. The results showed that mothers who consumed additional foods during breastfeeding were 2.9 times more likely to practice optimal breastfeeding compared to those who did not (OR=2.9; 95% CI: 1.33–6.44; p=0.007). Similarly, mothers who consumed nutritional supplements were 2.5 times more likely to engage in good breastfeeding practices (OR=2.5; 95% CI: 1.27–5.08; p=0.008). These findings indicate that dietary factors significantly influence breastfeeding practices. Promoting the consumption of additional foods and nutritional supplements during breastfeeding can enhance breastfeeding practices. Targeted interventions focusing on dietary improvements are essential to support maternal and child health in coastal communities